Degradation of hydroxychloroquine by electrochemical advanced oxidation processes - Nasr Bensalah (14778253) (2020)
In this work, the degradation of hydroxychloroquine (HCQ) drug in aqueous solution by electrochemical advanced oxidation processes including electrochemical oxidation (EO) using boron doped diamond (BDD) and its combination with UV irradiation (photo-assisted electrochemical oxidation, PEO) and sonication (sono-assisted electrochemical oxidation, SEO) was investigated. EO using BDD anode achieved the complete depletion of HCQ from aqueous solutions in regardless of HCQ concentration, current density, and initial pH value. The decay of HCQ was more rapid than total organic carbon (TOC) indicating that the degradation of HCQ by EO using BDD anode involves successive steps leading to the formation of organic intermediates that end to mineralize. Furthermore, the results demonstrated the release chloride (Cl−) ions at the first stages of HCQ degradation. In addition, the organic nitrogen was converted mainly into NO3− and NH4+ and small amounts of volatile nitrogen species (NH3 and NOx). Chromatography analysis confirmed the formation of 7-chloro-4-quinolinamine (CQLA), oxamic and oxalic acids as intermediates of HCQ degradation by EO using BDD anode. The combination of EO with UV irradiation or sonication enhances the kinetics and the efficacy of HCQ oxidation. PEO requires the lowest energy consumption (EC) of 63 kWh/m3 showing its cost-effectiveness. PEO has the potential to be an excellent alternative method for the treatment of wastewaters contaminated with HCQ drug and its derivatives. Other Information Published in: Chemical Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cej.2020.126279